The darker side of organizational citizenship behavior and its remedies - Han, Yong; Altman, Yochanan (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Whilst the extant literature on organizational citizenship behavior (OCB) extols its positive features, we wish to raise awareness to the negative consequences of those behaviors for individuals and groups as well as organizations, through the prism of management practices, specifically by reference to performance appraisal, compensation, and training and development. Our discussion focuses on how to minimize the individual, group and organizational costs of OCB, whilst simultaneously promoting task and OCB performance.